Labor Migration and Economic Growth in East and Southeast Asia - Walmsley, Terrie; Aguiar, Angel; Ahmed, S. Amer (World Bank, Washington, DC, 2014)
East and Southeast Asia face major demographic changes over the next few decades as many countries' labor forces will start to decline, while others will experience higher labor force growth as populations and participation rates increase. A well-managed labor migration strategy presents itself as a mechanism for ameliorating the impending labor shortages in some East-Asia Pacific countries, while providing an opportunity for other countries with excess labor to provide migrant workers that will contribute to the development of the home country through greater remittance flows. Although migration would be unable to offset the economic impacts of the declining labor forces in the countries with shrinking populations, a more flexible migration policy, allowing migrants to respond to the major demographic changes occurring in Asia over the next 50 years, would be beneficial to most economies in the region in terms of real incomes and real gross domestic product over the 2007-2050 period. Such a policy could deeply affect the net migration position of a country. Countries that were net recipients under current migration policies might become net senders under the more liberal policy regime.